Clinical analysis of 13 cases with growth hormone deficiency combined with pituitary stalk interruption - Wang, Gao-liang (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2010)
OBJECTIVE: To analyze the clinical characteristics of the patients with pituitary stalk interruption syndrome (PSIS), and to achieve better comprehension of this disease